IBU-IBU PKK TENTANG CARDIAC ARREST DI DESA LAUT DENDANG - Gertuda Tuti Wijayanti Waruwu; Rostime Hermayerni Simanullang (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Health education plays a very important role in influencing individual behavior to have appropriate knowledge and understanding. Cardiac arrest is a common event that is often unpredictable and has the potential to result in rapid death. This condition occurs when the heart's function suddenly stops, caused by the cessation of the heart's electrical activity and accompanied by respiratory arrest. The importance of increasing public knowledge in providing prehospital first aid, especially in recognizing the signs of cardiac arrest in adults and having the skills to perform cardiopulmonary resuscitation (CPR), becomes urgent. The importance of quick and appropriate treatment in emergency conditions can be realized through the role of laypeople who can become part of the chain of survival when encountering victims outside the hospital environment. Laypeople in the vicinity have great potential to find emergency cases, so their ability to quickly and accurately perform basic life-saving actions becomes very crucial. However, in reality, the knowledge and skills of laypeople before receiving education about handling Out Of Hospital Cardiac Arrest (OHCA) are still relatively low. Therefore, the role of education and training in the context of this research becomes very significant. Objective: To analyze the effect of education on the knowledge level of PKK (Family Welfare Program) mothers about cardiac arrest in Laut Dendang Village. Methods: This type of research is quantitative with a pre-experimental design using the one-group pre-test-post-test method. The sampling technique used Simple Random Sampling with 30 respondents. Data analysis was performed using the Wilcoxon signed-rank test. Results: The results of this study showed a significant effect of education on the knowledge level of PKK mothers in Laut Dendang Village about cardiac arrest, with a p-value of 0.000 < 0.05. Conclusion: There is an effect of education on the knowledge level of PKK mothers about cardiac arrest in Laut Dendang Village. Suggestion: Future research is recommended to relate the knowledge gained with other factors such as sources of information, social, and cultural influences to improve the quality of the research.